Comprehensive cytotoxicity studies of superparamagnetic iron oxide nanoparticles - Rakesh M. Patil; Nanasaheb D. Thorat; Prajkta B. Shete; Poonam A. Bedge; Shambala Gavde; Meghnad G. Joshi; Syed A.M. Tofail; Raghvendra A. Bohara (Biochemistry and Biophysics Reports, 2018)
Recently lots of efforts have been taken to develop superparamagnetic iron oxide nanoparticles (SPIONs) for biomedical applications. So it is utmost necessary to have in depth knowledge of the toxicity occurred by this material. This article is designed in such way that it covers all the associated toxicity issues of SPIONs. It mainly emphasis on toxicity occurred at different levels including cellular alterations in the form of damage to nucleic acids due to oxidative stress and altered cellular response. In addition focus is been devoted for in vitro and in vivo toxicity of SPIONs, so that a better therapeutics can be designed. At the end the time dependent nature of toxicity and its ultimate faith inside the body is being discussed. Keywords: SPIONs, Toxicity, Cellular alteration, Biomedical applications